Persistent SARS-CoV-2 Infection in a Patient With Non-hodgkin Lymphoma: Intra-Host Genomic Diversity Analysis - Bianco, Angelica; Capozzi, Loredana; Del Sambro, Laura; Simone, Domenico; Pace, Lorenzo; Rondinone, Valeria; Difato, Laura M.; Miccolupo, Angela; Manzari, Caterina; Fedele, Alberto; Parisi, Antonio (Frontiers in Virology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a pandemic, threatening global public health. Several cases of persistent infection have been described, but there are few reports that compared the genetic variability among samples collected from the patient during infection. In the current study, we reported a viral genetic analysis of a diabetic male patient with Non- Hodgkin Lymphoma affected by persistent SARS-CoV-2 infection. We sequenced the patient-derived viral isolated both from oro/nasopharyngeal swab and VeroE6 cell line, collected from the same patient at different points of the infection. Due to the insufficient material of the second swab received, in order to obtain a complete coverage of the viral genome, it was convenient to perform a virus isolation after cell culture. Both genomes belonged to Pangolin Lineage B.1, Nextstrain clade 20A and GISAID clade G. The mutation spectrum predicted for the two viral genomes reveal three additionally mutations in the sequence of second sample when compared with mutations set identified in the first sample. Our findings show the evolution of the intra-host variability during the course of a long-lasting infection.